Functional Outcome Of Proximal Humerus Plating In Displaced Proximal Humerus Fractures (Journal of Pharmaceutical Negative Results, 2022)
Background:The purpose of this study was to examine a group of patients who had fracture of the proximal part of the humerus, representative of the individuals who commonly sustain this fracture, treated by rigid internal fixation after a near anatomic reduction, emphasizing on the functional results, range of motion, strength, and complications.Methods: This is a prospective study , of 22 patients conducted at Meenakshi Medical College & Hospital, kanchipuram in Department of Orthopaedics on those who were admitted with displaced fracture of Proximal Humerus from July 2021 to August 2022.Results:The functional results after rigid fixation of fractures using a plate were shown to be better than conservative treatment or semi-rigid fixation without anatomical reduction of the head fragment. Shoulder function continued to improve as the strength and function of the muscles increased.Conclusion:Early fixation, exact anatomical repositioning of the fracture fragments and rigid internal fixation was associated with a significantly better functional results.